2014
DOI: 10.1038/cr.2014.150
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis of AMPK regulation by adenine nucleotides and glycogen

Abstract: AMP-activated protein kinase (AMPK) is a central cellular energy sensor and regulator of energy homeostasis, and a promising drug target for the treatment of diabetes, obesity, and cancer. Here we present low-resolution crystal structures of the human α1β2γ1 holo-AMPK complex bound to its allosteric modulators AMP and the glycogen-mimic cyclodextrin, both in the phosphorylated (4.05 Å) and non-phosphorylated (4.60 Å) state. In addition, we have solved a 2.95 Å structure of the human kinase domain (KD) bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
233
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(253 citation statements)
references
References 56 publications
18
233
1
1
Order By: Relevance
“…Additional study reported that CBM of β2 subunit binds more tightly to oligosaccharides than β1 subunit (Koay et al, 2010), and this may have physiological implications related to AMPK profile of skeletal muscle, in which β2 subunit is a predominant form. A recent analysis of low-resolution crystal structures of human AMPK bound to glycogen-mimic cyclodextrin further provided a structural basis for understanding the allosteric effect of glycogen on AMPK activity (Li et al, 2015). It was proposed that CBM is a highly dynamic part in the β subunit and closely interacts with the kinase domain of α subunit in the absence of carbohydrate, but addition of glycogen almost abolished this interaction, leading to inhibition of the enzyme activity (Li et al, 2015).…”
Section: Regulation Of Ampk By Glycogenmentioning
confidence: 98%
See 1 more Smart Citation
“…Additional study reported that CBM of β2 subunit binds more tightly to oligosaccharides than β1 subunit (Koay et al, 2010), and this may have physiological implications related to AMPK profile of skeletal muscle, in which β2 subunit is a predominant form. A recent analysis of low-resolution crystal structures of human AMPK bound to glycogen-mimic cyclodextrin further provided a structural basis for understanding the allosteric effect of glycogen on AMPK activity (Li et al, 2015). It was proposed that CBM is a highly dynamic part in the β subunit and closely interacts with the kinase domain of α subunit in the absence of carbohydrate, but addition of glycogen almost abolished this interaction, leading to inhibition of the enzyme activity (Li et al, 2015).…”
Section: Regulation Of Ampk By Glycogenmentioning
confidence: 98%
“…A recent analysis of low-resolution crystal structures of human AMPK bound to glycogen-mimic cyclodextrin further provided a structural basis for understanding the allosteric effect of glycogen on AMPK activity (Li et al, 2015). It was proposed that CBM is a highly dynamic part in the β subunit and closely interacts with the kinase domain of α subunit in the absence of carbohydrate, but addition of glycogen almost abolished this interaction, leading to inhibition of the enzyme activity (Li et al, 2015). These works are highly intriguing in terms that the allosteric inhibition of AMPK by glycogen may provide some molecular explanations for the above mentioned phenomena, in vivo inhibitory effect of glycogen on AMPK (Derave et al, 2000;Wojtaszewski et al, 2002;Wojtaszewski et al, 2003).…”
Section: Regulation Of Ampk By Glycogenmentioning
confidence: 99%
“…While some drugs show β-isoform selectivity, others can activate either β1 or β2 isoforms. While previous structures have revealed the drug-binding pocket of β1-containing AMPK [1,2], this report by Li et al [3] represents the first time that the β2 allosteric binding pocket has been visualized. Interestingly, the allosteric binding pockets of the two isoforms superimpose closely, suggesting a shared mechanism.…”
mentioning
confidence: 99%
“…However, a physiological role for the glycogen interac-tion has not been conclusively shown. Li et al reveal that the interaction between isolated CBM and KD can be reduced upon glycogen or CD binding to the CBM [3]. Blocking CD/glycogen binding by mutating residue W99 in the CBM partially reversed the reduction in CBM-KD interaction caused by glycogen/CD binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation